Orthodox Pleasures: Cononads, Tabu, Regime, Beyond Margins - Tereškinas, Artūras (Respectus Philologicus, 2001)
The article demonstrates the critical connection to Lithuanian science of literature, traditional strategies of discursivity, which help to hide interests of self over-weakness; the author's patois is directed opposite the "high literature canon", which is hegemonised, absoluted, mystificated, when uttered universalism is possession of other discourses and methods. The value politics do not tolerate the pop culture, as if was felt the long for the former "general strategies", reasoning about historical monolithic, general limits and meanings (V. Daujotytė works). It's maintained, that there is ability to resist against such "uniting" position just creating self-critical discourses, modernly determining the role of Lithuanian literature and culture, investigator. It's important to explain, which discourses help to appear for the new political / national spaces, which models of the fetishistic discursivity limit them, narrow the disperse of general identities.There are spoken out for the cultural studies as for the way out for new academical perceptivities and abilities to self expression.rinkiniui? Atsakymas: FORTHCOMING.
Keywords: -